Yanghe Decoction Suppresses the Experimental Autoimmune Thyroiditis in Rats by Improving NLRP3 Inflammasome and Immune Dysregulation - Ma, Bing’e; Chen, Dexuan; Liu, Yangjing; Zhao, Zhengping; Wang, Jianhua; Zhou, Guowei; Xu, Kun; Zhu, Taiyang; Wang, Qiong; Ma, Chaoqun (Frontiers in Pharmacology, 2021)
Inflammation is an important contributor to autoimmune thyroiditis (AT). Yanghe decoction (YH) is a traditional Chinese herbal formulation, the compound of which has various anti-inflammatory effects. It has been used for autoimmune diseases such as ankylosing spondylitis (AS) treatment. As autoimmune thyroid disease is well known to be associated with various autoimmune diseases, in this study we aimed to investigate the effects of YH on autoimmune thyroiditis in rats and elucidate the underlying mechanism. The experimental autoimmune thyroiditis (EAT) model was established by thyroglobulin (pTG) injections and excessive iodine intake. Thyroid lesions were observed using hematoxylin and eosin (H&E) staining and serum levels of TgAb, TPOAb, TSH, T3 and T4 levels were measured by ELISA. IL-35 levels were evaluated using real-time polymerase chain reaction (RT-PCR) and Th17/Treg balance in peripheral blood mononuclear cells (PBMCs) were determined applying flow cytometry and RT-PCR. Changes in Wnt/β-catenin signaling were evaluated using Western blot. Immunofluorescence staining and western blot were employed to examine NLRP3 inflammasome activation in the thyroid. The results showed that YH minimized thyroid follicle injury and decreased serum concentrations of TgAb, TPOAb, TSH, T3 and T4 in EAT model rats. The mRNA of IL-35 was increased following YH treatment. YH also increased the percentage of Treg cells, and decreased Th17 proportion as well as Th17/Treg ratio in PBMCs. Meanwhile, the mRNA levels of Th17 related cytokines (RORγt, IL-17A, IL-21 and IL-22) were suppressed and Treg related cytokines (FoxP3, TGF-β and IL-10) were promoted in PBMCs. Additionally, the protein expressions of Wnt-1 and β-catenin were enhanced following YH treatment. NLRP3 immunostaining signal and protein levels of IL-17, p-NF-κB, NLRP3, ASC, cleaved-Caspase-1, cleaved-IL-1β and IL-18 were downregulated in the thyroid after YH intervention. Overall, the present study demonstrated that YH alleviated autoimmune thyroiditis in rats by improving NLRP3 inflammasome and immune dysregulation.